Changes in soil microbial community functionality and structure in a metal-polluted site: The effect of digestate and fly ash applications - Garcia-Sánchez, M; Garcia-Romera, I; Cajthaml, T; Tlustoš, P; Száková, J (Journal of environmental management, 2015)
Soil from Trhové Dušníky (Příbram, Czech Republic) is characterized by its high polymetallic accumulations in Pb-Ag-Zn due to mining and smelting activities. In previous studies performed in our research group, we have evaluated the potential use of amendments that would reduce the mobility and availability of metals such as Hg. We have observed that the application of digestate and fly ash in metal-polluted soil has an impact in immobilizing these metals. However, until now we have lacked information about the effect of these amendments on soil microbial functionality and communities. The multi-contaminated soil was used to grow wheat in a pot experiment to evaluate the impact of digestate and fly ash application in soil microbial communities. Soil samples were collected after 30 and 60 days of treatment. The digestate application improved chemical attributes such as the content in total organic carbon (TOC), water soluble carbon (WSOC), total soluble carbon (C), total soluble nitrogen (N), and inorganic N forms (NO3(-)) as consequence of high content in C and N which is contained in digestate. Likewise, microbial activity was greatly enhanced by digestate application, as was physiological diversity. Bacterial and fungal communities were increased, and the microbial biomass was highly enhanced. These effects were evident after 30 and 60 days of treatment. In contrast, fly ash did not have a remarkable effect when compared to digestate, but soil microbial biomass was positively affected as a consequence of macro- and micro-nutrient sources applied by the addition of fly ash. This study indicates that digestate can be used successfully in the remediation of metal-contaminated soil.
Keywords: biomasa; Triticum; Fungi; Biomass; Nitrogen; Česká republika; uhlík; rtuť; houby; pšenice; látky znečišťující půdu; Mercury; popel uhelný; Soil Microbiology; Microbial Consortia; Coal Ash; Physiological diversity; Soil; Soil Pollutants; Microbial functionality; Czech Republic; Microbial biomass; hornictví; mikrobiální společenstva; kovy; Carbon; dusík; Soil pollution; půdní mikrobiologie; Metals; Amendments; půda; Mining; Communities structure